The Dutch National Research Agenda in perspective : A reflection on Research and Science Policy in practice - Molenaar, Henk; Rinnooy Kan, A. H. G., 1949-; Graaf, Beatrice de (Book collections on Project MUSE., 2017)
The Dutch National Research Agenda is a set of national priorities that are set by scientists working in conjunction with corporations, civil society organisations, and interested citizens. The agenda consolidates the questions that scientific research will be focused on in the coming year. This book covers the current status of the Dutch National Research Agenda and considers what changes and adjustments may need to be made to the process in order to keep Dutch national research at the top of the pack.